An Educational Program to Improve Self-Care in Heart Failure Patients - Hudiyawati, Dian; Nur Imamah, Ida; Sulastri, Sulastri; Musa, Mazlinda; Dewi, Siti Mutiara Sari; Astuti, Lia (Jurnal Berita Ilmu Keperawatan, 2025)
Knowledge of heart failure patients' self-care influences pa-tient adherence and readiness for independent care at home. Self-care enhancement is a significant focus of heart failure management programs. Efforts can be made by providing self-care education using conventional media and the web. The current study aimed to determine the effectiveness of education using web media and booklets on self-care in heart failure patients. This research was an experimental study with a pretest-posttest design. Eligible respondents will be divided into two groups. A web group was a group that was given self-care education through the web, and a booklet group was given education using booklets. The questionnaire used the Self-Care Heart Failure Index to measure the patient's self-care score. An Independent t-test was used to analyze differences in self-care scores in the two groups. Of 76 respondents in this study, >50% were male, and most were in the adult age range (36-55 years old). Based on the results of the inde-pendent t-test in both groups (web and booklet) showed a significant differ-ence in the mean self-care score (p-value = 0.001). It illustrates that web media is more effective than booklet media. Providing education using media that health workers follow up is important to do as an effort to improve self-care in heart failure patients.